A Case Report of Aggressive Angiomyxoma in Pregnancy: Do Hormones Play a Role? - Theofano Orfanelli; Chi-Son Kim; Sally F. Vitez; James Van Gurp; Neeti Misra (Case Reports in Obstetrics and Gynecology)
Aggressive angiomyxoma is a rare, locally invasive tumor that generally affects the perineum and pelvis of reproductive age females. Aggressive angiomyxoma is often misdiagnosed, resulting in the delay of the treatment. Case reports show increased growth of the tumor during pregnancy, thus suggesting a hormonal dependency. We report this rare condition in a 29-year-old primigravid female with a growing mass on the right labium majus at 20 weeks’ gestation. The patient also developed a smaller mass on the left labium majus at 37 weeks’ gestation. The patient underwent a primary cesarean section with resection of the right labial mass, with a final diagnosis of aggressive angiomyxoma. The lesion on her left labium majus resolved spontaneously postpartum. This case report supports a hormonal involvement in this tumor.